Crushed Stone Utilization in replacing Silica Sand in Ultra-High Performance Concrete - Pham, Sang Ngoc; Nguyen, Hung Dinh; Mai, Luu (Engineering, Technology & Applied Science Research, 2025)
Ultra-High Performance Concrete (UHPC) offers superior load-bearing capacity and durability, yet its reliance on natural Silica Sand (SS) contributes to high production costs and environmental concerns. This study examines the feasibility of substituting SS with Crushed Stone (CS) aggregates in UHPC production. Through a combination of theoretical analysis and experimental investigation, an optimal mixture is identified, and the effects of CS aggregates on key UHPC properties, including flowability, air bubble content, and compressive strength, are evaluated. The experimental results indicate that UHPC incorporating CS aggregates achieves compressive strengths exceeding 130 MPa at 28 days. The Scanning Electron Microscopy (SEM) analysis reveals that the Interfacial Transition Zone (ITZ) surrounding CS aggregates exhibits lower local stiffness due to the predominance of calcium hydroxide (CH) and ettringite crystals. Furthermore, the microstructural analysis identifies the presence of elongated particles (accounting for up to 32% of the mixture) and microcracks within the CS aggregates, which contribute to a reduction in compressive strength. Consequently, UHPC produced with CS aggregates achieves approximately 84% of the compressive strength of UHPC utilizing SS aggregates. Despite this reduction in mechanical performance, the cost-effectiveness of CS-based UHPC is significantly superior, with a 29% reduction in the overall production costs and a 16% improvement in the cost-to-performance ratio compared to SS-based UHPC. These findings demonstrate that CS aggregates provide a viable and economically advantageous alternative to SS in UHPC production, offering significant cost savings while maintaining the essential mechanical properties required for structural applications.